An Analysis of the Payrolls of the Point St.Charles Shops of the Grand Trunk Railway - Hoskins, Ralph (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1989)
This paper contains a summary of the methods used in, and the important findings of, an analysis of the payrolls of the Point St. Charles Shops of the Grand Trunk Raiiway for part of the period 1880-1917. The analysis was carried out under the following headings : ethnicity, hours of work and wages, persistence in the job and the journey to work.